Effect of formal training in scaling, scoring and classification of the International Standards for Neurological Classification of Spinal Cord Injury - Schuld, Christian; Wiese, Julia; Franz, Steffen; Putz, Cornelia; Stierle, Irma; Weidner, Norbert; Rupp, Rüdiger (Spinal cord, 2013)
Study Design:Prospective, longitudinal cohort study.Objectives:To quantify the effect of formal training in the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) on the classification accuracy and to identify the most difficult ISNCSCI rules.Settings:European Multicenter Study on Human Spinal Cord Injury (EMSCI).Methods:EMSCI participants rated five challenging cases of full sensory, motor and anorectal examinations before (pre-test) and after (post-test) an ISNCSCI instructional course. Classification variables included sensory and motor levels (ML), completeness, ASIA Impairment Scale (AIS) and the zones of partial preservation.Results:106 attendees were trained in 10 ISNCSCI workshops since 2006. The number of correct classifications increased significantly (P<0.00001) from 49.6% (2628 of 5300) in pre-testing to 91.5% (4849 of 5300) in post-testing. Every attendee improved, 12 (11.3%) achieved 100% correctness. Sensory levels (96.8%) and completeness (96.2%) are easiest to rate in post-testing, while ML (81.9%) and AIS (88.1%) are more difficult to determine. Most of the errors in ML determination arise from sensory levels in the high cervical region (C2−C4), where by convention the ML is presumed to be the same as the sensory level. The most difficult step in AIS classification is the determination of motor incompleteness.Conclusion:ISNCSCI training significantly improves the classification skills regardless of the experience in spinal cord injury medicine. These findings need to be considered for the appropriate preparation and interpretation of clinical trials in spinal cord injury.